PENGENDALIAN BAHAYA FAKTOR BIOLOGI MENGGUNAKAN MESIN VENTILASI UDARA MEKANIK DENGAN FILTER ANTIBAKTERI - Budi, M Sri Prasetyo; Gusmarwani, Sri Rahayu; Rauf, Muhammad (KURVATEK, 2022)
Indoor air quality with clean air as one of the basic factors could be obtained with adequate ventilation. Implementation of a ventilation machine equipped with a bio filter would improve the control of biological pollutants. The mechanical air ventilation machine was made 32 cm x 3.25 cm x 60 cm using an exhaust fan with a voltage of 220 Volts, a frequency of 50 Hz, a motor rotation of 1250 RPM, a volume wind (CFM) output speed of 450 CFM with a temperature of 25oC, equipped with 2 filters Car cabin air conditioner with bio-antibacterial liquid from green betel leaf filtrate and a liquid misting machine. Based on the results of chemical quality tests and air biological quality tests on mechanical air ventilation machines with 2 layers of filters, there is a significant difference in CO2 levels produced and the number of colonies in the exhaust air was below the threshold of 1000 CFU/m3 for fungi and 700 CFU/m3 for bacteria.